Memristor emulator circuits using single CBTA - Ayten, Umut Engin; Minaei, Shahram; Sagbas, Mehmet (ELSEVIER GMBH, 2017)
In this paper, new analog memristor emulator circuits based on current backward transconductance amplifier (CBTA) and passive elements are proposed. They emulate both types of memristor (incremental and decremental) just by interchanging the CBTA output terminals. It uses only one CBTA, two resistors, one capacitor and one multiplier emulating grounded memristor. They consist of less CMOS transistors and have wider output ranges compared to other designed emulator circuits. The CMOS implementation of the CBTA using 0.18 ttm level-7 TSMC CMOS technology parameters is also proposed. It uses 23 CMOS transistors operating with the +/- 0.9 V DC supply voltage. Theoretical derivations and related results are validated using SPICE simulations. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Electronics; Memristors; Current conveyors; Non-linear resistor; Current backward transconductance amplifier (CBTA); Engineering; Telecommunications